Web performance optimization basics (O'Reilly Media, Inc., 2019)
In today’s increasingly demanding online world, one of the quickest ways to drive existing or potential customers and users to a competitor is by having a nonperformant website or app. With users becoming more discerning, you need to ensure that you’re providing the best web experience possible. This reality has pushed performance optimization to be one of the most important disciplines in app and website development. Well-designed and smooth-performing apps and sites can lead to greater conversion rates and a better user experience (UX) in all contexts. In this video course, designed for intermediate-level developers with an understanding of HTML, CSS, JavaScript, and web technologies in general, your host Max Firtman, shows you some of the most important things you can do to boost the performance of your web assets. As the saying goes, you can’t fix what you can’t measure, so to begin, you’ll learn the important metrics to monitor and how to measure them. Max also shows you how to set goals for your web content, find issues that can negatively affect UX, and apply some basic techniques that will improve user perception. You’ll also benefit from practical examples and formative assessment to help you absorb and retain what you’ve learned. This video course is only the beginning of your optimization journey, so at the end we provide suggestions on how to continue along the path to delivering the best web assets you can.